PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2014) - Yohanna Bregiba Lolaninta Br Purba; Herry Laksito (Diponegoro Journal of Accounting, 2016)
This study investigates the impact of audit committee effectivity on financial distress. This study use three charachteristics of audit committee that is size of audit committee, frequency of audit committee meeting and competence of audit committee. This study use one control variable is leverage. Population that use in this study is 405 manufacture listed firms in Indonesia Stock Exchange in 2012-2014. Based on purposive sampling method, there are 210 samples that consist of 54 financially distressed firms and 156 non financially distressed firms. Financial distress criteria is measure by discriminant value by Altman modification (Z-score). Data analysis using logistic regression with SPSS 21. The result from this study show that frequency audit committee meeting has significant negative affect with financial distress